PELATIHAN MEMBUAT TELUR ASIN TERHADAP KETERAMPILAN PRAVOKASIONAL ANAK TUNANETRA - LEDY TIA, NINIS (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Pre-vocational skills are associated with skill that can bring rewards or income. Since the blind students have barriers in pre-vocational skills that these barriers have an impact on the results of vocational unfavorable skills. Blind students, whose vision (both eyes) do not function as a channel receiver of information in daily activities like normal people. Referring to the students’un optimal pre-vocational skills, so the stimulus is needed to make pre-vocational skills become properly and optimally. The purpose of this research is to improve blind students’ pre-vocational skills in SMPLB-A YPAB Surabaya. The research used pre-experimental Design, using One-Group Pre-Test and Post-Test design. The subjects of this research were 6 students. There were 6 meetings with 4 intervention in this research. The data were collected by using test and documentation. The collected data were analyzed by non-parametric statistical analysis using sign test. The result showed that there was increasing score of blind students’ vocational skills that was 57,91 in pre-test, and 82,50 in post-test for average. From result was analyzed by using sign test, it was found that Zobserved (ZH) was 2.251, while Ztable at 5% significant level for both sides was (Zt=1.96). Therefore, Ho is refused and Ha is accepted (1.96<2.251>1.96). Based on the research result, it can be concluded that there was the influence of salty eggs training on blind students’ pre-vocational skill of eighth grade in SMPLB-A YPAB Surabaya   Keywords: Pre-Vocational Skills, Making Salty Eggs